PENGARUH HARGA DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN EMINA GLOSSY STAIN (LIPTINT) DI KOTA BANJARMASIN - Noor Hidayati; Novia Nour Halisa; Nurul Wahyuni; Meilisa Anggreni Saragih (Business Administration, FISIP ULM, 2024)
This study aims to examine the impact of Price Perception and Product Quality on Purchasing Decisions for Emina Glossy Stain in Banjarmasin. Using a quantitative approach, the research targets consumers in Banjarmasin who have purchased Emina Glossy Stain. The sampling technique is non-probability sampling, specifically accidental sampling, with 100 respondents selected. Data was gathered through questionnaires, and multiple linear regression was used for analysis. The results show that Price has a significant partial effect on purchasing decisions, while Product Quality does not have a significant influence.